Rare bird documentation form for Glaucous Gull at Black Hawk Lake, 1995 - Huser, Bill F.et al (1995)
Rare bird documentation form for a Glaucous Gull at Black Hawk Lake in Sac County, IA on November 18, 1995. Epson - sheet feed